Rational Assessment of Physico-Chemical Parameters of Agricultural Soil from Selected Places of Banepa, Nepal - Khadka, Isha; Jyawali, Sanju; Paudel, Dasu Ram (Pragya Darshan प्रज्ञा दर्शन, 2023)
Physico-chemical parameters are among the basic attributes for the study of soil as they play a critical role in the assessment of soil health. In the present study, an attempt was made to study the physicochemical parameters in soil samples collected from six places of Banepa (Sinagal, Budole, Janagal, Chandeswori, Nayabasti, and Dhaneswor). The soil characterization was carried out for parameters like moisture content (%), pH, electrical conductivity (EC), chloride (Cl-), sulphate (SO42-), and phosphate (PO43-) ions. Chloride and sulphate were analyzed by argentometric titration and gravimetric method. The molybdenum blue method was employed for analysis of phosphate. In the present study, the pH of different soil samples ranged from 4.02-6.46 indicating a strongly to slightly acidic nature. EC values ranged from 0.05-0.45 mS/cm which showed that all soil samples were non-saline. The concentration of Cl-, SO42- and PO43- were in the range of 10142-16904 ppm, 1440-3907 ppm, and 1.8-3.8 ppm, respectively. Analysis of these parameters helps to determine the nature, fertility status of soil which is important for agricultural chemists for plant growth and soil management. Such studies provide the necessary information required to maintain optimum fertility year after year.